2021
DOI: 10.1002/pits.22541
|View full text |Cite
|
Sign up to set email alerts
|

Counselor and student perceptions of an mHealth technology platform used in a school counseling setting

Abstract: School psychologists and counselors with large caseloads struggle with delivery of high‐quality mental health services in the school setting due to time constraints and competing responsibilities. These providers can benefit from technology solutions that help engage and monitor the mental health of their clients in and out of session. This study assessed the usability and acceptability of a mobile health (mHealth) for the mental health technology platform, NeuroFlow, with seven students and three providers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…An interesting finding was that school psychologists were the counselor/interventionist in only 29% of the studies despite the fact that the studies were published in prominent school psychology journals. Although few in number, these studies demonstrated positive outcomes when school psychologists were interventionists (Angacian et al, 2015 ; Puhy et al, 2021 ; Sportman et al, 2010 ; Yeo et al, 2011 ). The majority of studies included outside clinicians/therapists that were not school-based employees delivering the services, which may make it challenging for school psychologists to translate these studies into practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting finding was that school psychologists were the counselor/interventionist in only 29% of the studies despite the fact that the studies were published in prominent school psychology journals. Although few in number, these studies demonstrated positive outcomes when school psychologists were interventionists (Angacian et al, 2015 ; Puhy et al, 2021 ; Sportman et al, 2010 ; Yeo et al, 2011 ). The majority of studies included outside clinicians/therapists that were not school-based employees delivering the services, which may make it challenging for school psychologists to translate these studies into practice.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies that met the inclusion criteria, school psychologists (including preservice and in-service practitioners) were the interventionist in 29% of the articles, school counselors were the interventionists in 29% of the articles, other types of clinicians and therapists were the interventionists in 41% of the articles, and the remaining articles had other professionals (i.e., teachers) implementing the counseling intervention. It should be noted that one study that implemented the counseling intervention virtually (telehealth) consisted of having both school psychologists and school counselors (i.e., Puhy, 2021 ).…”
Section: Empirical Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic, this literacy was included in school curricula (Aghazadeh et al, 2020) and encouraged school teachers to enhance their capacity to identify and surmount children's mental health problems (Ní Chorcora & Swords, 2022). After the pandemic, children's mental health literacy development is still school teacher responsibility (Horikawa et al, 2023; Puhy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%